2022
DOI: 10.3389/fnut.2022.789986
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Anticholinergic Drug Burden Index Score Negatively Affect Nutritional Status in Older Patients Without Dementia

Abstract: Introduction/AimAnticholinergic drugs, which have severe central and peripheric side effects, are frequently prescribed to older adults. Increased anticholinergic drug burden is associated with poor physical and cognitive functions. On the other side, the impact of anticholinergics on nutritional status is not elaborated in the literature. Therefore, this study was aimed to investigate the effect of the anticholinergic burden on nutrition.Materials and MethodsPatients who underwent comprehensive geriatric asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The authors concluded that medication reviews are of paramount importance in the management of older patients 34 . Ates Bulut and co‐workers showed that an increased anticholinergic drug burden was associated with impaired cognitive functions and a decreased nutritional status in elderly patients 35 . Even though anticholinergic effects were evaluated as a subcategory of PDIs (Table 2), we did not specifically assess patients' anticholinergic drug burdens, which must be considered a further limitation of the present study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The authors concluded that medication reviews are of paramount importance in the management of older patients 34 . Ates Bulut and co‐workers showed that an increased anticholinergic drug burden was associated with impaired cognitive functions and a decreased nutritional status in elderly patients 35 . Even though anticholinergic effects were evaluated as a subcategory of PDIs (Table 2), we did not specifically assess patients' anticholinergic drug burdens, which must be considered a further limitation of the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Even though anticholinergic effects were evaluated as a subcategory of PDIs (Table 2), we did not specifically assess patients' anticholinergic drug burdens, which must be considered a further limitation of the present study. Interventions to minimize MRPs, such as interdisciplinary psychiatric ward rounds with medication reviews 36 (with a particular focus on drugs with anticholinergic properties 35 ), should be tested in prospective randomized clinical trials in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Full‐text articles were sought and screened for 316 articles that appeared to meet the inclusion criteria. Seventy studies 6,13–81 were included in the systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…75,76 Although the effects of anticholinergic drugs on nutritional status have not yet been fully investigated, a cross-sectional study reported that the presence of anticholinergic burden is associated with the presence and increased risk of low nutrition in older patients. 77,78 In an observational study of 1490 older patients aged 65 years or older admitted to a convalescence rehabilitation ward in Japan, a comparison of nutritional status at discharge between those whose anticholinergic burden increased during hospitalization and those whose burden did not increase showed that the group with an increased anticholinergic burden had significantly worse nutritional status. 79 Although the mechanism has not been fully explored in this study, anticholinergic use may be associated with decreased food intake owing to decreased appetite.…”
Section: Effects Of Cholinergic Agonists and Anticholinergics On Nutr...mentioning
confidence: 99%
“…Some systematic reviews have reported that anticholinergic drugs increase the risk for cognitive decline, delirium, falls, the development of physical decline and frailty, and even hospitalization and death 75,76 . Although the effects of anticholinergic drugs on nutritional status have not yet been fully investigated, a cross‐sectional study reported that the presence of anticholinergic burden is associated with the presence and increased risk of low nutrition in older patients 77,78 . In an observational study of 1490 older patients aged 65 years or older admitted to a convalescence rehabilitation ward in Japan, a comparison of nutritional status at discharge between those whose anticholinergic burden increased during hospitalization and those whose burden did not increase showed that the group with an increased anticholinergic burden had significantly worse nutritional status 79 .…”
Section: Effect Of Drugs On the Nutritional Status Of Older Patientsmentioning
confidence: 99%